Attidude of Civil Servant toward the Service of the State Social Security Fund in Luang Prabang - LORBANCHEAUY , Chanh; KEOBOUALAPHETH , Soulideth; SOMSACKXAYSOMPHENG, Oulavieng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purposes of the research are: 1) to compare the knowledge of civil servants towards the benefit of social security fund by distinguishing the personal factors; 2) to study and compare the satisfaction of employees and civil servants with the service of the State Social Security Fund by distinguishing personal factors; and 3) to examine the correlation between the personal factors and the behavior of civil servants in using the services of the State Social Security Fund in Luang Prabang Capital. The sample group included 293 participants who are the members of the State Social Security Fund in Luang Prabang City. A questionnaire was used as the data collection tool, and the statistics for the analysis, included frequency, percentage, mean, standard deviation (SD), T-test, F-test, and Chi-square to test the statistical hypothesis. The results showed that 1) 293 civil servants in the Capital of Luang Prabang, Luang Prabang Province had an average moderate level of knowledge on benefits of the National Social Security Fund, accounting for 57.68%. When comparing the knowledge of civil servants to the knowledge of benefit of the State Social Security Fund by distinguishing the personal factors, it was found that age variations have different effects on their knowledge of the rights and benefits of the State Social Security Fund; 2) the level of satisfaction of civil servants towards the service of the State Social Security Fund is at a very high level. When comparing the satisfaction of civil servants to the service provided by the State Social Security Fund by distinguishing the personal factors, it was found that different ages affect the satisfaction of the State Social Security Fund and the rate of the combined payment. Different statuses affect the satisfaction of the State Social Security Fund, the combined rate, and the service location. The aspects of receiving benefits and the service process are different; different levels of education result in different levels of satisfaction with benefits; the average monthly income varies, resulting in different satisfaction rates and benefits, 3) the correlation between the personal factors and the behavior of civil servants in using the services of the State Social Security Fund in Luang Prabang Capital revealed that the gender is related to the behavior of the number of times to use the service per year and the time off from work when using the service; age is related to length of coverage and reasons for medical treatment that social security cards do not cover; status is also related to the behavior of the period of time to use the service, the period of insurance, and the reason for treatment with the hospital that the social security card does not cover and reasons for medical treatment that the social security cards do not cover; status is related to the behavior of the period of time to use the service, the period of insurance, and the reason for treatment with the hospital that the social security card does not cover; level of education is related to the behavior of the number of times to use the service per year, the period of time to use the service, and the period of insurance; average monthly income has a correlation with the behavior during the time to use the social security fund service and the absence from work during the time to use the service.